Pengaruh Konten Marketing Pada Media Sosial Tiktok Terhadap Minat Beli Produk Fashion Dewasa Studi pada: Calon Konsumen Pasar Besar Nongkojajar Pasuruan - Ken Albarqi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
The development of information technology has changed the business landscape, encouraging traditional businesses to adopt digital marketing. This study aims to analyze the influence of marketing content—which includes informative, creative, and interactive aspects—on social media TikTok on the purchasing interest of adult fashion products. This study focuses on potential consumers in the Nongkojajar Market, Pasuruan, with TikTok as the mediating variable. This study uses a descriptive quantitative approach. The sample consisted of 100 respondents selected through purposive sampling, with the criteria of being over 17 years of age, interested in fashion products, and active TikTok users. Primary data was collected through an online questionnaire. Data analysis was conducted using validity, reliability, classical assumption, and path analysis tests. The results showed that all instruments were valid and reliable. Partially, creative (p=0.002) and interactive (p=0.002) content had a significant effect on TikTok usage. Similarly, informative content (p=0.017) and creative content (p=0.003) were found to have a significant effect on purchase intention, while interactive content and the TikTok platform itself were not significant. However, simultaneously, all four variables (informative, creative, interactive content, and TikTok) had a significant effect on purchase intention (p=0.000). This research model explains 26.1% of the variation in purchase interest. In conclusion, the effectiveness of marketing on TikTok is highly dependent on the quality of the content presented, where informative and creative content are key factors that drive consumer purchase interest in traditional markets.